2014
DOI: 10.5121/ijsea.2014.5502
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influncing Quality of Mobile Apps: Role of Mobile App Development Life Cycle

Abstract: In this paper, The mobile application field has been receiving astronomical attention from the past few years due to the growing number of mobile app downloads and withal due to the revenues being engendered .With the surge in the number of apps, the number of lamentable apps/failing apps has withal been growing.Interesting mobile app statistics are included in this paper which might avail the developers understand the concerns and merits of mobile apps.The authors have made an effort to integrate all the cruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(73 citation statements)
references
References 10 publications
1
62
0
4
Order By: Relevance
“…A mobile application is software designed to run on smart phones, tablets and other mobile devices [12]. The purpose of these applications is interacting with users, especially in the case of games and are more like a computer program than a website [13].…”
Section: Mobile Applicationsmentioning
confidence: 99%
“…A mobile application is software designed to run on smart phones, tablets and other mobile devices [12]. The purpose of these applications is interacting with users, especially in the case of games and are more like a computer program than a website [13].…”
Section: Mobile Applicationsmentioning
confidence: 99%
“…The most important aspect of a requirements elicitation technique is its ability to transfer knowledge from users to analysts [7], [8]. Developers should allow users to take part in the elicitation process in the original design and subsequent iterations of the project as studies have shown that 44% of users will immediately delete applications with poor performance [9]. The Wizard of Oz (WOz) technique is a low-fidelity prototyping technique where software requirements are simulated to give an impression of how these requirements will work when actually implemented.…”
Section: Introductionmentioning
confidence: 99%
“…The first and foremost reason for low quality mobile application development is that app developers are not conforming to the development life cycle phases [5]. Other reasons include: lack of experience on the app development SDKs, and not enough testing is done.…”
Section: Development Processmentioning
confidence: 99%
“…The phases of the SDLC include: analysis, design, implementation, and testing. Each phase is itself composed of a series of steps, which rely on techniques that produce deliverables [5].…”
Section: Introductionmentioning
confidence: 99%